CAN PERCEIVED WORK-LIFE BALANCE AND WORKLOAD ENHANCE EMPLOYEE PERFORMANCE? EMPIRICAL EVIDENCE FROM PT CAHYA DELIVERY INDONESIA - Kabul Wahyu Utomo; Riandy Saputra; Sri Yusriani; Novika Purnama Sari; Heffi Christya Rahayu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study investigates the effects of perceived work-life balance (PWLB) and workload on employee performance, with job satisfaction functioning as a mediating variable, at PT Cahya Delivery, a logistics and service distribution company operating in Sumatra, Indonesia. The research was motivated by a decline in employee performance observed in 2024, accompanied by heightened workload demands during peak delivery periods. A quantitative research design was employed, utilizing structured questionnaires administered to 190 active employees selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results demonstrate that PWLB exerts a significant positive influence on both job satisfaction and employee performance. Conversely, workload shows a negative direct effect on performance but an unexpected positive effect on job satisfaction, suggesting that increased responsibilities may enhance perceived trust and motivation among employees. Job satisfaction was found to partially mediate the relationships between both exogenous variables and employee performance. These findings underscore the strategic importance of fostering work-life balance and carefully managing workload structures to enhance employee satisfaction and performance. The study provides actionable insights for human resource management in the logistics service sector, particularly in designing challenge-oriented workloads and support mechanisms to sustain productivity and organizational effectiveness.